Life cycle assessment of bio-based sodium polyacrylate production from pulp mill side streams: case study of thermo-mechanical and sulfite pulp mills. (10th September 2016) - Gontia, Paul; Janssen, Matty
Abstract: Sodium polyacrylate (Na-PA) is a super absorbent polymer, which is commonly used in diverse hygiene products. The polymer is currently produced from fossil feedstock and its production consequently leads to adverse environmental impacts. Na-PA production from sugars present in pulp mill side streams can potentially be a successful way to achieve a more sustainable production of this polymer. In order to guide the development of a novel biochemical process for producing Na-PA, a life cycle assessment was done in which Na-PA produced from side streams of thermo-mechanical pulp (TMP) and sulfite pulp mills were compared. Furthermore, a comparison was made with Na-PA produced from fossil resources. The results show that the main determinant of the environmental impact of the bio-based Na-PA production is the free sugar content in the side streams. The lowest environmental impact is achieved by the least diluted side streams. More diluted side streams require larger amounts of energy for concentration, and, if the diluted streams are not concentrated, processes such as hydrolysis and detoxification, and fermentation are the environmental hotspots. Furthermore, the higher the yield of the fermentation process, the lower the environmental impact will be. Lastly, the production of bio-based Na-PA led to a lower global warming potential for some of the considered pulp mill side streams, but all of the other impacts considered were higher, when compared to fossil-based Na-PA production. Therefore, in parallel with efforts to develop a high-yield yeast for the fermentation process, technology developers should focus on low energy concentration processes for the side streams.